KEMAMPUAN MENGIDENTIFIKASI UNSUR PEMBANGUN TEKS DRAMA PADA SISWA KELAS XI SMA GAJAH MADA BANDAR LAMPUNG - Salamah Salamah; Desnia Verlinda; Idawati Idawati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
This article discussed the limited problems namely: lack of the ability to identify intrinsic elements of drama texts in class XI of even semester students at Gajah Mada High School in Bandar Lampung. This study aims to determine the ability identifying intrinsic elements of drama texts in class XI students of SMA Gajah Mada Bandar Lampung. The research used a qualitative descriptive method, namely by identifying students' abilities in determining intrinsic elements of drama texts in accordance with indicators such as themes, mandate, plot/plot, character/ characterization, setting/setting, perspective, language style. In this study, 30 samples from 150 existing populations were determined and random sampling was taken. Based on the results of research was conducted by the author through data collection techniques using test techniques, namely students were given the task of drama text and determine intrinsic elements, that the level of students ability to identify intrinsic elements of drama text of XI grade students of Gajah Mada High School in Bandar Lampung as a whole can be said to be very good with indicators as follows: (1) determining the theme in the criteria is very well, (2) determining the mandate in the criteria is very well, (3) determining the flow in the criteria is very well, (4) determining the character / characterization in the criteria is very well, (5) determining the setting is in good criteria, (6) determining the point of view is in sufficient criteria, (7) determining the style of language is in sufficient criteria.